2011
DOI: 10.3748/wjg.v17.i42.4647
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and management of non-steroidal anti-inflammatory drugs-induced small intestinal injury

Abstract: Non-steroidal anti-inflammatory drug (NSAID)-induced small bowel injury is a topic that deserves attention since the advent of capsule endoscopy and balloon enteroscopy. NSAID enteropathy is common and is mostly asymptomatic. However, massive bleeding, stricture, or perforation may occur. The pathogenesis of small intestine injury by NSAIDs is complex and different from that of the upper gastrointestinal tract. No drug has yet been developed that can completely prevent or treat NSAID enteropathy. Therefore, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 52 publications
0
52
0
16
Order By: Relevance
“…NSAID-induced enteropathy and bleeding occur more frequently that NSAID-induced gastropathy [2,3] . Significant small intestinal damage and bleeding can be observed in about 70% of chronic NSAID users [4,5] , and in the majority of patients the injury is sub-clinical [6] . Unlike the case for NSAID-gastropathy, there are no proven-effective preventative therapies for NSAIDenteropathy, and the pathogenesis is poorly understood [7] .…”
Section: Overview Of the Clinical Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…NSAID-induced enteropathy and bleeding occur more frequently that NSAID-induced gastropathy [2,3] . Significant small intestinal damage and bleeding can be observed in about 70% of chronic NSAID users [4,5] , and in the majority of patients the injury is sub-clinical [6] . Unlike the case for NSAID-gastropathy, there are no proven-effective preventative therapies for NSAIDenteropathy, and the pathogenesis is poorly understood [7] .…”
Section: Overview Of the Clinical Problemmentioning
confidence: 99%
“…Unlike the case for NSAID-gastropathy, there are no proven-effective preventative therapies for NSAIDenteropathy, and the pathogenesis is poorly understood [7] . Iron-deficient anemia is a common first presentation of NSAID-enteropathy, and serious complications can include massive bleeding, perforation and strictures, sometimes leading to death [2,6,8] .…”
Section: Overview Of the Clinical Problemmentioning
confidence: 99%
“…Often, these may be provided for a concomitant or a related disorder. For example, non-steroidal anti-inflammatory drugs (NSAIDs) [45] are often used in patients with ankylosing spondylitis or other arthropathy associated with inflammatory bowel disease. Sometimes, these agents have been associated with a wide range of small intestinal pathological changes, including ulceration and stricture formation that, in some instances, may be even difficult to distinguish from an underlying intestinal disorder, such as CD.…”
Section: Medication-related Causesmentioning
confidence: 99%
“…As regards small bowel diaphragms produced by NSAIDs, this has resulted in the retention of the videocapsule at a rate of 1.1% in 1,000 patients with various indications for examination with endoscopic videocapsule analyzed in a retrospective study [16]. Characteristic diaphragm-like strictures are said to be a result of chronic ulcers caused by NSAID, and in this regard it has been reported that 17% of patients with NSAID-induced small bowel ulcers can develop such stenoses [17]. On the other hand, the rate of non-excretion was zero in healthy asymptomatic volunteers [18].…”
Section: Discussionmentioning
confidence: 99%